STXBP1 encephalopathy: A neurodevelopmental disorder including epilepsy. (8th March 2016) - Stamberger, Hannah; Nikanorova, Marina; Willemsen, Marjolein H.; Accorsi, Patrizia; Angriman, Marco; Baier, Hartmut; Benkel-Herrenbrueck, Ira; Benoit, Valérie; Budetta, Mauro; Caliebe, Almuth; Cantalupo, Gaetano; Capovilla, Giuseppe; et al.
Abstract : Objective: To give a comprehensive overview of the phenotypic and genetic spectrum of STXBP1 encephalopathy ( STXBP1 -E) by systematically reviewing newly diagnosed and previously reported patients. Methods: We recruited newly diagnosed patients with STXBP1 mutations through an international network of clinicians and geneticists. Furthermore, we performed a systematic literature search to review the phenotypes of all previously reported patients. Results: We describe the phenotypic features of 147 patients with STXBP1 -E including 45 previously unreported patients with 33 novel STXBP1 mutations. All patients have intellectual disability (ID), which is mostly severe to profound (88%). Ninety-five percent of patients have epilepsy. While one-third of patients presented with Ohtahara syndrome (21%) or West syndrome (9.5%), the majority has a nonsyndromic early-onset epilepsy and encephalopathy (53%) with epileptic spasms or tonic seizures as main seizure type. We found no correlation between severity of seizures and severity of ID or between mutation type and seizure characteristics or cognitive outcome. Neurologic comorbidities including autistic features and movement disorders are frequent. We also report 2 previously unreported adult patients with prominent extrapyramidal features. Conclusion: De novo STXBP1 mutations are among the most frequent causes of epilepsy and encephalopathy. Most patients have severe to profound ID with little correlation among seizure onset, seizure severity, and the degree of ID. Accordingly, we hypothesize that seizure severity and ID present 2 independent dimensions of the STXBP1 -E phenotype. STXBP1 -E may be conceptualized as a complex neurodevelopmental disorder rather than a primary epileptic encephalopathy.